A Mutual Broadcast Authentication Protocol for Wireless Sensor Networks Based on Fourier Series - Xiaogang Wang; Weiren Shi (International Journal of Distributed Sensor Networks)
This thesis presents a mural broadcast authentication protocol (MBAP) for wireless sensor networks based on Fourier series according to the issues of the main broadcast authentication protocol µ TESLA being limited in authentication delay, more initial parameters, limited time, large key chain, and network congestion. Firstly, achieving the forward authentication work for common sensor nodes to base station is based on the characteristic of continuous-integrability function f ( x ) in [ - π , π ] which could be expanded into Fourier series, including entity authentication and source attestation. Secondly, assume that f ( x ) is the quadratic form function, and achieve the reverse authentication work for base station to common sensor nodes by detecting the security of f ( x ) . The analysis results of safety performance in MBAP show that the captured nodes in WSN will not affect the security of broadcast authentication protocol and have low computation and communication cost, the base station can make broadcast randomly, and common sensor nodes can authenticate messages instantly, which solves the problem of network congestion well. The most important thing of MBAP is the mutual broadcast authentication method which ensures the security of the network greatly.